Effects and Mechanisms of Symbiotic Microbial Combination Agents to Control Tomato Fusarium Crown and Root Rot Disease - Cai, Xinyue; Zhao, Honghai; Liang, Chen; Li, Min; Liu, Runjin (Frontiers in Microbiology, 2021)
This study evaluated the effects and underlying mechanisms of different combinations of plant symbiotic microbes involving arbuscular mycorrhizal fungi (AMF), plant growth-promoting rhizobacteria (PGPR) and Trichoderma spp. on tomato Fusarium crown and root rot (TFCRR). A total of 54 treatments were designed in a greenhouse pot experiment with tomato cv. Ginobili seedlings inoculated with or without Funneliformis mosseae (Fm), Rhizophagus intraradices (Ri), Trichoderma virens l40012 (Tv), Trichoderma harzianum l40015 (Th), Bacillus subtilisPS1-3 (Bs), Pseudomonas fluorescens PS2-6 (Pf), and Fusarium oxysporum f. sp. Radicis-lycopersici (Fo). The symbioses on the tomato root systems were well developed, and the composite symbiont constructed by AMF + Trichoderma spp. was observed for the first time. Compared with other treatments, Ri + Bs + Tv and Fm + Pf + Tv showed better improvements in tomato plant growth and yield. Ri + Pf + Th + Fo gave the best biocontrol effects on TFCRR, followed by Th + Pf + Fo and Ri + Th + Fo. While compared with Fo treatment, most of the inoculation treatments improved photosynthetic performance, and significantly increased the defensive enzyme activity in tomato plants, with Ri + Pf + Th + Fo showing the highest activity value. Metabolome analysis showed changes in a total of 1266 metabolites. Numbers of up-regulated metabolites in tomato plants inoculated with Ri + Pf + Th, and Ri + Pf + Th + Fo were more than that of Fo, while the down-regulated was just opposite. It is concluded that AMF + Trichoderma + PGPR combination has a greater effect on inducing plant disease resistance. The up-regulation and down-regulation of metabolites regulated by symbiotic genes may be an important mechanism for these root symbiotic microorganisms to promote plant growth, increase yield and improve disease resistance.